The Effect of Non-Pharmacological Intervention on Self-Efficacy in Stroke Patients - Ikha Nurjihan; Fitria Handayani; Meira Erawati (Media Keperawatan Indonesia, 2022)
Stroke sufferers are faced with limitations both in terms of physical, psychological, and social aspects which cause sufferers to experience difficulties in carrying out activities. The cause of these difficulties is low self-efficacy which will have a negative impact on the health conditions and behavior of stroke sufferers. The purpose of the review is to describe how interventions related to self-efficacy and their effect on self-efficacy in stroke patients. The method used is scoping review by looking for relevant articles using keywords. The inclusion criteria in this review were participants with a diagnosis of stroke, the results of the study measured self-efficacy, the study was a randomized controlled trial, the year of publication was in the 2011-2021 period, and the study was in English. The results in the review are five articles that have significant results on self-efficacy and six articles have insignificant results. Articles that have significant results apply interventions with several strategies including education, training, motivation, and self-management. The conclusion of this review is an article that has significant results in implementing a complex intervention (SESSMP intervention, MSE training intervention, and self-management empowerment intervention) and a single intervention (Health Empowerment Intervention for Stroke Self-management and SFBT).